Genomic Mechanisms of Physiological and Morphological Adaptations of Limestone Langurs to Karst Habitats. (21st December 2019) - Liu, Zhijin; Zhang, Liye; Yan, Zhongze; Ren, Zhijie; Han, Fengming; Tan, Xinxin; Xiang, Zhiyuan; Dong, Fang; Yang, Zuomin; Liu, Guangjian; Wang, Ziming; Zhang, Jiali; et al.
Abstract: Knowledge of the physiological and morphological evolution and adaptation of nonhuman primates is critical to understand hominin origins, physiological ecology, morphological evolution, and applications in biomedicine. Particularly, limestone langurs represent a direct example of adaptations to the challenges of exploiting a high calcium and harsh environment. Here, we report a de novo genome assembly (Tfra_2.0) of a male François's langur ( Trachypithecus francoisi ) with contig N50 of 16.3 Mb and resequencing data of 23 individuals representing five limestone and four forest langur species. Comparative genomics reveals evidence for functional evolution in genes and gene families related to calcium signaling in the limestone langur genome, probably as an adaptation to naturally occurring high calcium levels present in water and plant resources in karst habitats. The genomic and functional analyses suggest that a single point mutation (Lys1905Arg) in the α1c subunit of the L-type voltage-gated calcium channel Cav 1.2 (CACNA1C) attenuates the inward calcium current into the cells in vitro. Population genomic analyses and RNA-sequencing indicate that EDNRB is less expressed in white tail hair follicles of the white-headed langur ( T. leucocephalus ) compared with the black-colored François's langur and hence might be responsible for species-specific differences in body coloration. Our findings contribute to a new understanding of gene–environment interactions and physiomorphological adaptative mechanisms in ecologically specialized primate taxa.